Simvastatin nanoliposome induces myocardial and hepatic toxicities due to its absorption enhancement in mice - Nuerbiye Tuerdi; Gulinigaer Anwaier; Xing Zhang; Shu Liu; Wanli Shen; Wen Liu; Qiang Shen; Rong Qi (Elsevier, 2020)
Nanoliposome is a useful dosage form to increase solubility and absorption of simvastatin (SMV), and consequently improves its therapeutic effects. However, in vivo toxicity of SMV could also be elevated accompanied by the absorption enhancement, which is a decisive factor for the clinical application of SMV nanoliposome (SMV-Lipo), but has not been studied systematically and reported so far. In this study, organ toxicity of SMV-Lipo was evaluated in mice in the presence and absence of isoproterenol and compared to those of free SMV. Results demonstrated that compared to free SMV, the SMV-Lipo administrated at an equal dose of 25 mg/kg/d led to severe myocardiotoxicity, hepatotoxicity at baseline and more pronounced liver injury with elevation of alanine aminotransferase. In addition, muscular adverse effect was also observed in SMV-Lipo treated group but not in SMV group. Pharmacokinetic studies revealed that compared to free SMV, the SMV-Lipo administration significantly improved the plasma SMV concentration, and the oral bioavailability was 6.5 times of free SMV. Notably, when the dosage of free SMV increased to 50 mg/kg/d, yielding the comparable plasma concentration as SMV-Lipo given at 25 mg/kg/d, the myocardiotoxicity was observed in free SMV treated mice as well, which further confirmed that the enhanced absorption of SMV by the nanoliposomal formulation resulted in more severe myocardiotoxicity than the equal dose of free SMV. Keywords: Simvastatin, Nanoliposome, Myocardiotoxicity, Muscular toxicity, Hepatotoxicity